2010
DOI: 10.1186/1752-1947-4-222
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of uterine leiomyosarcoma: a case report

Abstract: IntroductionMalignant change in a leiomyoma or uterine fibroid is termed leiomyosarcoma. It arises from smooth muscle of the uterus and is a rare tumor that accounts for 2% to 5% of all uterine malignancies. Very few cases are reported in the literature. Our patient did not have any history of genital bleeding, which is the usual presentation in uterine sarcoma. We report an original case report of an unusual presentation of this rare tumor arising from the uterus.Case presentationA 40-year-old nulliparous wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 5 publications
1
21
1
Order By: Relevance
“…Senol et al reported a very large leiomyosarcoma in a 62-year-old female presenting with abdominal mass, fatigue, and associated tenderness [ 16 ]. Vellanki et al also reported a uterine leiomyosarcoma in a 40-year-old nulliparous woman presenting with abdominal pain and no menstrual irregularity and no vaginal bleeding [ 17 ]; our patient had no vaginal bleeding and no abdominal pain, just complains from 3 months' period of abdominal distension attributed to gastrointestinal diseases. However, abdominal distension is usually attributed to gastrointestinal diseases which leads to misdiagnosis, mismanagement, and overgrowth of tumor [ 18 ].…”
Section: Discussionmentioning
confidence: 56%
“…Senol et al reported a very large leiomyosarcoma in a 62-year-old female presenting with abdominal mass, fatigue, and associated tenderness [ 16 ]. Vellanki et al also reported a uterine leiomyosarcoma in a 40-year-old nulliparous woman presenting with abdominal pain and no menstrual irregularity and no vaginal bleeding [ 17 ]; our patient had no vaginal bleeding and no abdominal pain, just complains from 3 months' period of abdominal distension attributed to gastrointestinal diseases. However, abdominal distension is usually attributed to gastrointestinal diseases which leads to misdiagnosis, mismanagement, and overgrowth of tumor [ 18 ].…”
Section: Discussionmentioning
confidence: 56%
“…[10] Vellanki et al reported a case of pelvic mass with raised CA125, which on histology was diagnosed as uterine leiomyosarcoma. [11] Local control of soft tissue sarcomas is usually achieved with surgical resection. Pre operative planning based upon radiographic and pathologic information is important to ensure adequate surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…In postmenopausal women, the incidence of sarcoma is 1%–2% and they have a rapid doubling time of 4 weeks 2. Uterine leiomyosarcoma behave aggressively with a high rate of recurrence and poor prognosis 3.…”
Section: Differential Diagnosismentioning
confidence: 99%